IDNLearn.com connects you with a community of experts ready to answer your questions. Discover prompt and accurate responses from our experts, ensuring you get the information you need quickly.
Sagot :
Answer:
y = 6
x = 5
Step-by-step explanation:
-6x + 6y = 6
-6x + 3y = - 12
Multiply the second equation by -1, then add the equations;
-6x + 6y = 6
6x - 3y = 12
___________
3y = 18
/3 /3
y = 6
x = 5
We value your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. IDNLearn.com is committed to providing accurate answers. Thanks for stopping by, and see you next time for more solutions.
For What Values Of The Variable Is Each Rational Expression Undefined2x-3/2x-1( Step By Step Please)